Correlation between Trichomonas vaginalis and Concurrency: An Ecological Study - Kenyon, Chris R.; Hamilton, Deven T. (Interdisciplinary Perspectives on Infectious Diseases, 2016)
Objective. There is a large variation in the prevalence of Trichomonas vaginalis (TV) between different countries and between racial groups within countries. Sexual partner concurrency may play a role. We investigate the correlation between the prevalence of sexual partner concurrency and TV prevalence. Methods. Spearman’s correlation to assess relationship between TV prevalence in women and point prevalence of concurrency in men in (1) 11 countries with comparable data (concurrency data from WHO Survey and TV prevalence data from Global Burden of Disease estimates) and (2) three racial groups in the United States (Add Health Study). Results. The prevalence of TV and concurrency was positively correlated in the international (rho = 0.84, P=0.001) and USA study (rho = 1.0, P<0.001). Conclusion. Prospective longitudinal studies that include measures of partner behavior are required to definitively establish the role of concurrency in the spread of TV.